2023
DOI: 10.1101/2023.09.25.559317
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nutritional condition drives spatial variation in physiology of Antarctic lipid-storing copepods

Cory A. Berger,
Deborah K. Steinberg,
Ann M. Tarrant

Abstract: Lipid-rich copepods form an essential link between primary producers and higher trophic levels in high-latitude oceans. These zooplankton can take advantage of ephemeral phytoplankton blooms to fuel development and reproduction. However, we have limited understanding of how the physiological condition of these animals varies in relation to environmental factors such as food availability. Due to high advection, it is likely that physiological plasticity, rather than local adaptation, is primarily responsible fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…However, due to logistical constraints, we could not always remove some small algal cells (<3 microns) from the starved treatments. Nonetheless, changes in physiological condition, gene expression, and the correlation of our experimental response with field chlorophyll measurements reported in Berger et al (2023) indicate that our starvation treatment captured a bona fide response to food deprivation.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…However, due to logistical constraints, we could not always remove some small algal cells (<3 microns) from the starved treatments. Nonetheless, changes in physiological condition, gene expression, and the correlation of our experimental response with field chlorophyll measurements reported in Berger et al (2023) indicate that our starvation treatment captured a bona fide response to food deprivation.…”
Section: Discussionmentioning
confidence: 55%
“…Clade-level analyses also found evidence for low dN/dS in CSGs across the copepod phylogeny. Starvation-response genes had less variable expression than other genes in our paired field study (Berger et al, 2023) while having similar dispersion across species, strongly suggesting the action of stabilizing selection on expression level (Price et al, 2022). While purifying selection on sequence and stabilizing selection on expression need not go hand in hand, we found that genes under strong coding constraint tend to have less expression variability among individuals (Fig.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…To address how metabolic gene expression varies across environmental conditions and experimental feeding manipulations, we sequenced and assembled transcriptomes for C. acutus and C. propinquus. In an accompanying paper, we report patterns of gene expression and other physiological metrics spanning the PAL-LTER study region (Berger et al, 2023b).…”
Section: Introductionmentioning
confidence: 99%